SUPPLYING THE POPULATION WITH DRINKING WATER AND EFFECTIVE MANAGEMENT OF THE WASTEWATER SYSTEM (Archive of Conferences, 2022)
This article deals with the provision of drinking water to the population and effective management of the wastewater system. The author clarified the problem on the basis of existing literature, relying on economic data and scientific sources. A comparative analysis of existing specific approaches and theories for the provision of drinking water and effective management of wastewater systems